2015
DOI: 10.7314/apjcp.2015.16.16.7039
|View full text |Cite
|
Sign up to set email alerts
|

S100A16 is a Prognostic Marker for Lung Adenocarcinomas

Abstract: Background: Many functional molecules controlling diverse cellular function are included in low-molecular weight proteins and peptides. Materials and Methods: To identify proteins controlling function in lung adenocarcinomas (AC), we performed two-dimensional gel electrophoresis employing tricine-SDS polyacrylamide in the second dimension (tricine 2-DE). This system was able to detect proteins under 1 kDa even with posttranslational modifications. To confirm the utility of detected proteins as novel tumor mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…There are no reports on the expression of S100A16 in cervical carcinoma. It has been reported that a high S100A16 expression level is correlated to poor prognosis in breast cancer and lung adenocarcinoma (27,28), whereas a low S100A16 expression level is correlated with reduced survival and poor tumor differentiation in oral squamous cell carcinoma (29). Further studies are needed to clarify the function of S100A16 and its clinical significance in the various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports on the expression of S100A16 in cervical carcinoma. It has been reported that a high S100A16 expression level is correlated to poor prognosis in breast cancer and lung adenocarcinoma (27,28), whereas a low S100A16 expression level is correlated with reduced survival and poor tumor differentiation in oral squamous cell carcinoma (29). Further studies are needed to clarify the function of S100A16 and its clinical significance in the various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the co‐expression of S100A14 and S100A16 correlated with a poor prognosis in human breast cancer and promoted the invasive activity of breast cancer cells via an interaction with cytoskeletal dynamics (Sapkota et al , ). High S100A16 expression was found to be significantly associated with a poor prognosis in lung, prostate and breast cancers (Saito et al , ). Conversely, recent studies reported that the decreased expression of S100A16 predicts poor prognosis in oral squamous cell carcinoma (OSCC) and colorectal cancer (Sapkota et al , ; Sun et al , ).…”
mentioning
confidence: 99%
“…We previously reported that S100A10 and S100A16 are expressed in a subset of lung adenocarcinoma [10,11]. In the present study, 164 patients were enrolled.…”
Section: Evaluation Of Relationship Between S100a14 Expression and Otmentioning
confidence: 99%
“…We evaluated the relationship between S100A14 expression and S100A10 or S100A16 expression in the 164 patients. The procedures for immunohistochemical staining and evaluation of staining for S100A10 and S100A16 were described in our previous study [10,11].…”
Section: Evaluation Of Relationship Between S100a14 Expression and Otmentioning
confidence: 99%
See 1 more Smart Citation